Distribution of E.coli O157:H7 in fecal and urine samples of cattle: : E.coli O157:H7, Cattle, Fecal, Urine - Al-Rudha, Aseel M H (The Iraqi Journal of Veterinary Medicine, 2016)
This study was designed to isolate of Enterohaemoragic E.coli O157:H7 from feces and urine in cattle. 175 samples (80 fecal and 95 urine) were collected to isolate EHEC O157:H7 during the period from March to June 2014 from Al- Hindia slaughter house from local breeding cattle, aged between 1-2 years and over 2 years, and the samples were subjected to culture on specific media Cefixime Tellurit- Sorbitol MacConkey agar at 37 ˚C for 18-24 hrs. then the isolates were identified by biochemical tests (Indol test, Potassium cyanid test) and seriologically by Latex Kit test. The results showed that 73(91.25%) out of 80 fecal samples and 39(41%) out of 95 urine samples were E.coli O157:H7 positive, the total of positive isolates were 64%. That reveals the important role of feces and urine samples to contaminate the environment and disseminate of infection.